Anthropomorphism and the Apophatic God - Insole, Christopher J. (Modern theology, 2001)
This paper is a warning-shot across more sloppy contemporary invocations of an apophatic God. Such apophatic approaches are thought to avoid anthropomorphic projections onto God of parochial and problematic notions of the human subject. Developing an analysis of two views of the human subject given by Charles Taylor, I suggest that modern constructions of the apophatic God look very much like a projection of an intellectually-compromised and culturally-pervasive notion of the subject. I call this subject the "romantic monad", suggesting Ally McBeal as an example.